Selection of essential materials in social studies subjects through a differentiated approach according to Carol Tomlinson - Kristy, Grisyelda Tabitha; Alviani, Adistia Akses; Kusuma, Evita Rizki; Apriliana, Imroatul; Nabida, Luxnaya; Sayidina, Miastika Nur; Parahita, Bagas Narendra; Siregar, Riadi Syafutra (Asatiza: Jurnal Pendidikan, 2024)
One of the key elements of the Merdeka Curriculum is the implementation of essential materials, which are deemed crucial and must be delivered to students. However, limited research has focused on essential materials within social studies subjects. Therefore, it is necessary to conduct an in-depth analysis of how teachers apply essential materials in social studies. Based on this need, the objective of this study is to analyze the selection of essential materials by social studies teachers using a differentiated approach, as proposed by Carol Tomlinson. This research employs a Systematic Literature Review (SLR) method, gathering secondary data sources relevant to the research topic. The data consists of journal articles from 2019 to 2024, retrieved using Harzing's Publish or Perish software. The subjects of this study are high school social studies teachers, with a focus on their practices in teaching essential materials. The findings reveal that teachers have selected essential materials that are both relevant and engaging for students. This is evidenced by the use of learning media that resonates with students' daily lives, as well as digital-based teaching methods such as problem-based learning (PBL), gamification, and field studies. As a result, students are able to easily grasp the material, enhancing their motivation, conceptual understanding, and engagement in the learning process.